Epidemiological profile of snakebites in the Brazilian state of Minas Gerais (Research, Society and Development, 2022)
The objective of this work is to review studies regarding ophidian accidents in Minas Gerais, tracing the epidemiological profile in this State, besides characterizing the venomous animals snakes, types and genus, signs and symptoms of their inoculation, and clinical aspects and treatment of this disease. A literature review was performed with bibliographic research in the MedLine and SciELO databases. It is possible to observe that the Brazilian snakes of public health interest are those of the families Viperidae and Elapidae, and the ophidian accidents are divided into: snakes genus Bothrops, snakes genus Crotalus, snakes genus Lachesis and snakes genus Micrurus. The diagnosis of the victim of snakebite is based on clinical-laboratory changes and identification of the snake type, but rarely does the victim take the animal that caused the snake to the hospital so that health professionals can identify the species and perform the treatment for each type of venom. Serotherapy is performed to maintain patient normality and prevent worsening of symptoms. According to the revised epidemiological profile of the State of Minas Gerais, most of the accidents occurred with Bothrops snakes, followed by Cotralus, in rural areas during work or leisure, usually in males between the ages of 20 and 50, in hot and rainy months, with the feet and legs most affected. Most of the victims sought medical attention within one to three hours, receiving snake antivenom serum, with few deaths and complications. These results are shown in accordance with other studies in the medical-scientific literature.